The Anthropologist's Body or What It Means to Break Your Neck in the Field - Biddle, Jennifer L. (The Australian journal of anthropology, 1993)
Today the rider wore no smiles. She was tired, or head-achy, or involved in relationships with human beings. (Patrick White, The Tree of Man)